Diversity, Growth, and Understanding: School Responses to Immigration in Rural New Brunswick - Hamm, Lyle D.; Bragdon, Marc; McLoughlin, John; Massfeller, Helen; Hamm, Lauren A. (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation, 2021)
The province of New Brunswick is growing its population through immigration and retention strategies of newcomers to grow and stabilize its economy. Many communities, traditionally unaccustomed to such growth, are now experiencing a rapid shift in their ethnocultural populations. This report is based on a case study research conducted in three rural New Brunswick schools in three closely connected communities. Each school is confronting their own issues with the shift in their student demographics, but all share common strengths and challenges. The researchers identified four main intersecting themes, each connected to a sub-theme. They found that: 1). Newcomer students are striving hard to learn and live in an English culture; 2). Newcomer students are working to belong in their school through finding Canadian-born friends and allies; 3). Educators and newcomer students are mindful that deficit thinking hinders language and verbal communication; and 4). Stereotypical perceptions about new immigrants taking jobs away from New Brunswickers are pervasive and consistent in the schools and communities that were studied. As more newcomers arrive in the province, the researchers advocate that educators and school leaders need more knowledge and support for working with newcomer students and families. Further, deeper conversations about stereotyping and racism will need to occur to effectively eradicate the negative perceptions about immigrants and immigration in the province.